Factors Influencing Perceptions of Pay Fairness Among Millennial Employees in Technology Startups - Oktarina Harahap; M Chaerul Rizky; M Zaidan Thalhah Nasution; Mochamad Fachrul Rozy; Rezqy Agusta Sangkong; Roy Batoran Siagian (Universitas Dehasen Bengkulu, 2026)
Perceived pay fairness is a strategic aspect of human resource management, particularly in technology startups dominated by millennial employees. Millennials tend to value transparency, fairness, and alignment between their work contributions and compensation. This study aims to analyze the factors influencing perceptions of pay fairness among millennial employees in technology startups. A quantitative research approach was employed using a survey method through questionnaires. The variables examined include payroll system transparency, salary suitability to workload, career developsment opportunities, and salary comparison with coworkers. The findings indicate that payroll transparency and salary-workload suitability have the most significant influence on perceived pay fairness. Meanwhile, career development and salary comparison also affect perceptions of fairness, although to a lesser extent. This study is expected to provide valuable insights for startup management in designing fair, transparent, and sustainable compensation systems.